1990
DOI: 10.1121/1.399955
|View full text |Cite|
|
Sign up to set email alerts
|

Articulation rate and the duration of syllables and stress groups in connected speech

Abstract: Further analyses have been made on readings of two scripts by six talkers [T. H. Crystal and A. S. House, J. Acoust. Soc. Am. 72, 705-716 (1982); 84, 1932-1935 (1988); 83, 1553-1573 (1988)]. Durations of syllables and stress groups are compared to earlier data and various pertinent published reports, and are used to evaluate reports of articulation rate variability. The average durations of syllables of different complexity have a quasilinear dependency on the number of phones in the syllable, where the linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
0
7

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(117 citation statements)
references
References 0 publications
10
100
0
7
Order By: Relevance
“…These results are in agreement with observations made for English (Crystal & House, 1990;Jacewicz et al, 2010). However, it is important to note that the differences we have observed between the regional variants do not depend on the speaking style.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are in agreement with observations made for English (Crystal & House, 1990;Jacewicz et al, 2010). However, it is important to note that the differences we have observed between the regional variants do not depend on the speaking style.…”
Section: Discussionsupporting
confidence: 82%
“…It has been claimed that AR is faster in reading than in conversation (Grosjean & Deschamps, 1975;Lucci, 1983). However, some studies present an inverse tendency (Avanzi, Schwab, Dubosson & Goldman, 2012;Crystal & House, 1990;Woehrling, Boula de Mareüil & Adda-Decker, 2008). Moreover, it has been shown that the length of the utterance affects AR (Bartkova 1991;Quené, 2008): the longer the utterance, the faster the AR 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the stressed syllables were, on average, 310 msec long, and the unstressed syllables were all approximately 185 msec long. This ratio (1.67:1) is a close match with Crystal and House's (1990) report of the ratio of stressed CV syllables to unstressed CV syllables in the fluent speech of a fast talker (1.85:1).…”
Section: Methodssupporting
confidence: 74%
“…Listeners have been shown to use these changes in duration in segmenting sequences of repeated syllables (Nakatani & Schaffer, 1978). However, because other factors such as phonetic, prosodic, discourse level, and interspeaker variation also affect the duration of segments and syllables, duration cues may not be sufficiently reliable to allow the segmentation of connected speech (for further discussion of sources of variation in segment and syllable duration, see Anderson & Port, 1994;Crystal & House, 1990;Klatt, 1976).…”
Section: Acoustic Cues To Word Boundariesmentioning
confidence: 99%